La homofobia como factor de creación de identidades sexuales - Bustos, Alberto (CUADERNOS KÓRE, 2012)
Homophobic discourses have played a key role in the emergence of a homosexual identity. Since the Middle Ages they have contributed to putting the focus on homosexuality as the marked pole of the opposition heterosexuality/homosexuality. On the other hand, heterosexuality (being the unmarked, "normal" element) has usually escaped a more attentive scrutiny. This differential focus on one of the elements has blurred the role of homophobia in the construction of the heterosexual identity as hegemonic identity that presents itself as non existent. Some of the clues to homophobia might nevertheless lie in ambivalent and grey areas of heterosexual identity itself.